Depression, Neuroticism and 2D:4D Ratio: Evidence from a Large, Representative Sample - Leopold Maria Lautenbacher; Levent Neyse (Scientific Reports, 2020)
A body of literature reports higher rates of depression and neuroticism in female samples compared to male samples. Numerous studies have investigated the role of prenatal sex hormone exposure in this sex difference, using the ratio between the second and fourth digit of the hand (“2D:4D”) as a putative marker. However, the sample sizes of those studies were mostly small and results remained inconclusive. The aim of the present study is to test the suggested associations between depression, neuroticism and the 2D:4D ratio in a large, representative sample of over 3,000 German individuals. It was hypothesized that a higher 2D:4D (supposedly representing a more “feminine” prenatal hormone exposure) would positively predict (1) one's history of depression as well as (2) neuroticism rates and (3) acute depressive symptom scores. Controlling for biological sex, we only found suggestive evidence for linear associations with neuroticism in the case of left hand 2D:4D ratios and the mean 2D:4D of both hands. However, additional analyses indicated that these results may have been spurious due to confounding. Our findings suggest that the 2D:4D ratio is not a relevant predictor of depression, while there was mixed evidence in the case of neuroticism.
Keywords: 330; Endocrinology; Predictive markers; Psychology